A Study of Problems and Needs for Strengthening Competencies in Effective Teaching and Learning Management among Teachers at Mosque-Based Islamic Education Centers (Tadika) in the Three Southern Border Provinces of Thailand - Khareng, Mutsalim; Machae, Rohanee (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2026)
DOI : 10.14456/pnuhuso.2026.13 This research is a quantitative study with three objectives: (1) to examine the problems and obstacles in teaching and learning management among teachers at mosque-based Islamic education centers (Tadika); (2) to examine the needs of teachers at the mosque-based Islamic education centers (Tadika) for strengthening their competencies in classroom teaching and learning management; and (3) to propose a model for strengthening teaching and learning management competencies of teachers at the mosque-based Islamic education centers (Tadika) in order to promote students’ reading, writing, and analytical thinking skills. The instruments used in this research consisted of: (1) a questionnaire with a reliability coefficient of 0.725, which was administered to a sample of 1,051 teachers from the mosque-based Islamic education centres (Tadika), selected from a total population of 12,263 teachers in 1,771 mosque-based Islamic education centres (Tadika). The sample comprised 346 teachers from Yala Province, 351 from Pattani Province, and 354 from Narathiwat Province. The sample size was determined using the Krejcie and Morgan theory. The research data were analysed using descriptive statistics, namely means and standard deviations. (2) In addition, a set of evaluation instruments was used to assess the appropriateness and feasibility of the teaching and learning management competency enhancement model. These evaluation instruments were administered to a specific group of 10 experts. The data were analysed using descriptive statistics, namely means and standard deviations. The research findings indicated that: (1) the problems and obstacles in teaching and learning management among teachers at mosque-based Islamic education centres (Tadika) in all three provinces were at a low level. The mean scores were 2.47 (SD = 0.79) in Narathiwat Province, 2.44 (SD = 0.75) in Yala Province, and 2.43 (SD = 0.75) in Pattani Province. (2) The needs of teachers at mosque-based Islamic education centres (Tadika) for strengthening competencies in classroom teaching and learning management in all three provinces were at a high level. The mean scores were 4.35 (SD = 0.79) in Narathiwat Province, 3.95 (SD = 0.77) in Yala Province, and 4.34 (SD = 0.75) in Pattani Province. (3) The teaching and learning management competency enhancement model for teachers at mosque-based Islamic education centres (Tadika) showed a high level of appropriateness (Mean = 4.03, SD = 0.64) and a highest level of feasibility (Mean = 4.45, SD = 0.69).